PERANAN STRATEGI KOMUNIKASI PEMASARAN GRAND PURI WATER PARK DALAM MENARIK JUMLAH PENGUNJUNG - , AYU EFY KAMMALA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Every company is trying to find and establish their marketing strategies and marketing target. This condition is also happens in Grand Puri Water Park which is the largest Water Park in Yogyakarta. Based on the fact above, the researcher wants to know the marketing strategies that applied in Grand Puri Water Park. This research is also wants to know the problem faced Grand Puri Water Park in applying the marketing communication strategies. The researcher uses qualitative data research method, and the data obtained based on the results of observations, interviews, participation, and literature studies. The marketing strategies using the marketing communication tools that are parts of integred marketing communication (IMC). Holiday factor is also affects to increase the number of the guests. In other hand, the factors impede to decrease the number of the guests are limited promotion, lacks of cost, and lacks of human resources.